2018
DOI: 10.1016/j.midw.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of pregnancy related pelvic girdle pain: A systematic review

Abstract: Health professionals working with pregnant and postnatal women need to be aware of the anger, frustration and negative emotions resulting from PGP. These women may become socially isolated and there is a risk they could abuse analgesics in attempt to manage the pain especially if they do not have the social support. For women with young children, it is important to be aware of safety issues they face with carrying babies and controlling toddlers. It is therefore important that health professionals recognise PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 51 publications
5
70
0
1
Order By: Relevance
“…Pain impacted on all aspects of their life, including restrictions to ADL's and their psychosocial health, which is consistent with previous studies [2][3][4][5][6][12][13][14][15][16][28][29][30]. All participants described PPGP onset as insidious and within the second trimester.…”
Section: The Reality Of Ppgpsupporting
confidence: 89%
See 1 more Smart Citation
“…Pain impacted on all aspects of their life, including restrictions to ADL's and their psychosocial health, which is consistent with previous studies [2][3][4][5][6][12][13][14][15][16][28][29][30]. All participants described PPGP onset as insidious and within the second trimester.…”
Section: The Reality Of Ppgpsupporting
confidence: 89%
“…Given its impact upon pain and psychosocial health [12][13][14][15][16] in one fifth of pregnancies [1], safe, effective and acceptable interventions for PPGP are required. To date, acupuncture has shown promising results for PPGP [7] and appears to be safe [17], but has yet to be investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Biological measures. (Mackenzie et al, 2018). The EPDS is a 10-item measure; possible scores range from 0 to 30, with higher scores indicative of more symptoms of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers found that pregnant women with pelvic girdle pain often have concomitant pelvic floor myofascial pain (Fitzgerald & Mallinson, 2012), and pelvic floor muscle dysfunction can persist after childbirth (Handa, Blomquist, McDermott, Friedman, & Munoz, 2012). Persistent pelvic pain after childbirth has been shown to significantly affect quality of life (Mackenzie, Murray, & Lusher, 2018;Woolhouse, Gartland, Perlen, Donath, & Brown, 2014). Pelvic pain that begins after childbirth can become chronic over time and can lead to significant functional limitations and altered sexual function and can adversely affect future decisions about having more children (Bergströ m, Persson, Nergå rd, & Mogren, 2017;Lawson & Sacks, 2018).…”
mentioning
confidence: 99%
“…Although speed is a recommended expression of overall gait performance, quantification of spatiotemporal and kinematic gait characteristics might elucidate mechanisms involved in function (Lord et al, 2013). Early treatment of PGP is recommended (Mackenzie et al, 2018). Hence, knowledge of gait kinematics in the 2nd trimester of pregnancy may improve clinical management of PGP.…”
Section: Introductionmentioning
confidence: 99%